Hydrogen accommodation in the TiZrNbHfTa high entropy alloy. (1st May 2022) - Moore, C.M.; Wilson, J.A.; Rushton, M.J.D.; Lee, W.E.; Astbury, J.O.; Middleburgh, S.C.
Abstract: The equiatomic TiZrNbHfTa high entropy alloy (HEA) and its hydrides (TiZrNbHfTaH0.4- 2.0 ) have been modelled at the atomic scale and the phase transformations that occur during hydrogen absorption have been simulated. The thermodynamics of vacancy formation, hydrogen accommodation and hydride decomposition have been examined using density functional theory, linking results to experimental investigations. A model predicting the decomposition of the TiZrNbHfTaH system is proposed based on the temperature dependence of configurational and vibrational entropy terms and the hydrogen solution energies of individual interstitials. The presence of hydrogen in the HEA structure was shown to promote the formation of vacancies due to a 0.21 eV reduction of the energy barrier for vacancy formation. Interstitials placed around vacancies were observed to relax onto octahedral sites from initial tetrahedral positions, while interstitials placed in the same environment, without the vacancy present, were observed to relax onto tetrahedral sites from initial octahedral positions. This provides a mechanistic basis for experimentally observed behaviour. The phase stabilities of each arrangement of the TiZrNbHfTaH structure were explored, identifying that the FCC arrangement of the dihydride at the hydrogen to metal atom ratio (H/M) = 2.0, is more stable than the BCT arrangement at 550 K. The spontaneous BCC to BCT transformation, observed in the H/M range 1.2 – 1.6, and the thermodynamically favourable BCT to FCC phase transformation at H/M = 2.0, provides a comprehensive depiction of the mechanistic behaviour of the TiZrNbHfTa HEA during hydrogen absorption. Graphical abstract: Image, graphical abstract